Expectations' Anchoring and Inflation Persistence - Bems, Rudolfs (IMF Working Papers; Working Paper ;, 2018)
Understanding the sources of inflation persistence is crucial for monetary policy. This paper provides an empirical assessment of the influence of inflation expectations' anchoring on the persistence of inflation. We construct a novel index of inflation expectations' anchoring using survey-based inflation forecasts for 45 economies starting in 1989. We then study the response of consumer prices to terms-of-trade shocks for countries with flexible exchange rates. We find that these shocks have a significant and persistent effect on consumer price inflation when expectations are poorly anchored. By contrast, inflation reacts by less and returns quickly to its pre-shock level when expectations are strongly anchored.